![image](https://tex.z-dn.net/?f=%28y%20%2B%202%29%20%7B%7D%5E%7B2%7D%20%20-%20%28y%20%20%2B%202%29%20-%2012%20%3D%200%20%5C%5C%20%20%7By%7D%5E%7B2%7D%20%20%2B%204y%20%2B%204%20-%20y%20-%202%20-%2012%20%3D%200%20%5C%5C%20%20%7By%7D%5E%7B2%7D%20%2B%203y%20-%2010%20%3D%200%20%5C%5C%20d%20%3D%209%20-%204%20%5Ctimes%201%20%5Ctimes%20%28%20-%2010%29%20%3D%209%20%2B%2040%20%3D%2049%20%3E%200.%20%5C%3A%207.%20%5C%5C%20x1%20%3D%20%20%5Cfrac%7B%28%20-%203%29%20%2B%207%7D%7B2%7D%20%20%20%3D%20%20%5Cfrac%7B4%7D%7B2%7D%20%20%3D%202.%20%5C%5C%20x2%20%3D%20%20%5Cfrac%7B%28%20-%203%29%20-%207%7D%7B2%7D%20%20%3D%20%20%5Cfrac%7B%20-%2010%7D%7B2%7D%20%20%3D%20%20-%205.)
0. \: 7. \\ x1 = \frac{( - 3) + 7}{2} = \frac{4}{2} = 2. \\ x2 = \frac{( - 3) - 7}{2} = \frac{ - 10}{2} = - 5." alt="(y + 2) {}^{2} - (y + 2) - 12 = 0 \\ {y}^{2} + 4y + 4 - y - 2 - 12 = 0 \\ {y}^{2} + 3y - 10 = 0 \\ d = 9 - 4 \times 1 \times ( - 10) = 9 + 40 = 49 > 0. \: 7. \\ x1 = \frac{( - 3) + 7}{2} = \frac{4}{2} = 2. \\ x2 = \frac{( - 3) - 7}{2} = \frac{ - 10}{2} = - 5." align="absmiddle" class="latex-formula">
Ответ : х = -5 ; 2.
Удачи))))